Acute carbohydrate ingestion does not influence the post-exercise iron-regulatory response in elite keto-adapted race walkers - McKay, A. K. A.; Peeling, P.; Pyne, D. B.; Welvaert, M.; Tee, N.; Leckey, J. J.; Sharma, A. P.; Ross, M. L. R.; Garvican-Lewis, L. A.; van Swelm, R. L.; Laarakkers, C. M.; Burke, L. M. (Journal of Science and Medicine in Sport, 2019)
Objectives: Adhering to a low carbohydrate (CHO) high fat (LCHF) diet can alter markers of iron metabolism in endurance athletes. This investigation examined the re-introduction of CHO prior to, and during exercise on the iron-regulatory response to exercise in a homogenous (in regard to serum ferritin concentration) group of athletes adapted to a LCHF diet. Design: Parallel groups design. Methods: Three weeks prior to the exercise trials, twenty-three elite race walkers adhered to either a CHO-rich (n = 14) or LCHF diet (n = 9). A standardised 19-25 km race walk was performed while athletes were still adhering to their allocated dietary intervention (Adapt). A second test was performed three days later, where all athletes were placed on a high CHO diet (CHO Restoration). Venous blood samples were collected pre-, post- and 3 h post-exercise and measured for interleukin-6 (IL-6) and hepcidin-25. Results: The post-exercise IL-6 increase was greater in LCHF (p < 0.001) during both the Adapt (LCHF: 13.1-fold increase; 95% CI: 5.6-23.0, CHO: 8.0-fold increase; 5.1-11.1) and CHO Restoration trials (LCHF: 18.5-fold increase; 10.9-28.9, CHO: 6.3-fold increase; 3.9-9.5); outcomes were not different between trials (p = 0.84). Hepcidin-25 concentrations increased 3 h post-exercise (p < 0.001), however, they did not differ between trials (p = 0.46) or diets (p = 0.84). Conclusions: The elevated IL-6 response in athletes adapted to a LCHF diet was not attenuated by an acute increase in exogenous CHO availability. Despite diet-induced differences in IL-6 response to exercise, post-exercise hepcidin levels were similar between diets and trials, indicating CHO availability has minimal influence on post-exercise iron metabolism.